Herbicides registered for control of infesting plants in the cultive of Glycine max (L.) Merr. (soybeans) in Brazil (Research, Society and Development, 2022)
Chemical management is the most used in soybean crop to control weedplants. Thus, the registration of a herbicide must follow standards for its production, import, export, marketing and consumption, in addition to its effects on agriculture, health and the environment, and the Ministry of Agriculture, Livestock and Supply (MAPA) is the body that grants the federal registry and to obtain legal protection, the patent application must be filed with the National Institute of Industrial Property (INPI). The aim of this study was to trace the scenario of patenting herbicides registered and marketed for soybean crop in Brazil, during the years 2012 to 2022. For this, the patent was searched in the plant protection system (Agrofit) base of mapa. According to Agrofit, a total of 1,005 herbicides for soybeans were registered, since 1989 alone, during the period studied alone, 647 products whose marketing was associated with 56 companies were registered, especially: Rainbow Defensivos Agrícolas Ltda.; Dow Agrosciences Industrial Ltd.; UPL of Brazil Industry and Trade of Agricultural Insumuous S.A.; Adama Brasil S.A. and Nortox S.A. The increase in soybean production has leveraged the herbicide market, awakening research for the development of new compounds to be registered and marketed, mainly due to the resistance of weed plants to herbicides.